Physiological Effects of Heat Stress on Cardiac Function - Raghad Hasan Nafal,; Mohammed Hayder Asker, (American Journal of Biomedicine and Pharmacy, 2026)
Heat stress is a significant environmental and physiological issue that breaks thermoregulatory equilibrium and exerts significant force on the cardiovascular system. Increases in heart rate, changes in vascular tone, and changes in autonomic control are all quick responses of the heart to increases in body temperature which can ensure circulatory stability. Rabbits like humans have similar anatomical and physiological characteristics that make them a great model to study these effects because of their similarity in myocardial structure, coronary circulation, and autonomic regulation. In this review, the authors provide a summary of the cardiac effects of heat stress on rabbits incorporating systemic, cellular, and molecular evidence. Exposure to heat causes extreme tachycardia, low stroke volume, peripheral vasodilation, and changes in the electrocardiogram. At the cellular response, thermal stress triggers oxidative mechanisms, resulting in amplified release of reactive oxygen species, lipid peroxidation, compromised antioxidant mechanisms, and dysfunctional mitochondria. Also, thermal shock proteins of which HSP70 and HSP90 are the most important, is a critical protective response in maintaining cardiac proteins, mitochondrial functionality, and reducing apoptosis with prolonged or extreme exposure.Histopathological studies in rabbits have found a continuum of reversible swelling to structural degeneration of the myocardium. Since these reactions are highly similar to human physiological responses to heat, the rabbit model should be a useful translational marker of heat-related cardiovascular risk, particularly in relation to climate change, occupation, and exertional hyperthermia. The knowledge of these mechanisms can help in coming up with preventive and treatment measures to reduce cardiac predisposition in the face of heat stress.